(untitled) (The Pakistan Development Review, 2021)
This note provides overwhelming evidence that currency undervaluation is beneficial for economic growth. A macro-econometric model shows that the SBP continually used our scarce foreign exchange reserves to keep the exchange rate arbitrarily overvalued throughout history. This is one important factor that has contributed to our repeated BOP crises and IMF programmes. We hope that this note will inform the exchange rate policy to keep an undervalued target exchange rate and not use reserves to fight overvaluation (see also Jalil, 2020).